2011
DOI: 10.1007/s00468-011-0615-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sap velocity on the daytime increase of stem CO2 efflux from stems of Schima superba trees

Abstract: Stem CO 2 efflux (E s ) has been estimated from a temperature-related equation, but sap flux often affects measurements of E s , which leads to misunderstanding real stem respiration. In order to observe the relationship between E s and stem temperature and to analyze the effect of sap velocity on E s , stem temperature, E s and sap flux were measured from a subtropical Schima superba plantation in South China on three trees for consecutive 3 days in July and October 2009. Stem temperature, E s and sap velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…At our experimental site, S. superba trees grew all year round due to good water and heat condtions. The high temperature and soil moisture promoted the metabolic activity and increased the transpiration rate, which transported CO 2 from soil upwards, increasing stem CO 2 efflux at the monitored position (Zhu et al, 2012). Besides, annual mean LAI in this S. superba plantation reached 4.3, which could assimilate more energy from sunlight and provide sufficient substrate for stem respiration and then result in more CO 2 diffusion into the atmosphere.…”
Section: Vertical Variation Of Co 2 Efflux Along the Stemmentioning
confidence: 83%
See 2 more Smart Citations
“…At our experimental site, S. superba trees grew all year round due to good water and heat condtions. The high temperature and soil moisture promoted the metabolic activity and increased the transpiration rate, which transported CO 2 from soil upwards, increasing stem CO 2 efflux at the monitored position (Zhu et al, 2012). Besides, annual mean LAI in this S. superba plantation reached 4.3, which could assimilate more energy from sunlight and provide sufficient substrate for stem respiration and then result in more CO 2 diffusion into the atmosphere.…”
Section: Vertical Variation Of Co 2 Efflux Along the Stemmentioning
confidence: 83%
“…Additionally, it suggested that the respiring tissue was associated with the xylem cells (Levy and Jarvis, 1998;Meir and Grace, 2002;Cavaleri et al, 2006). This may be because (1) about 90 % of the stem, and (2) the living cells of the xylem tissue were very active in this S. superba plantation based on the high transpiration rates under the condition of sufficient water supply, which was reflected by the sap velocity of 0.83 and 0.41 g s −1 in the wet and dry season, respectively (Zhu et al, 2012). Teskey et al (2008) found that the distribution of living tissue cells between the bark and xylem depended on species and tree size.…”
Section: Stem Co 2 Efflux At the Stand Levelmentioning
confidence: 92%
See 1 more Smart Citation
“…Levy et al (1999) reported efflux rates between 6.0 (day time) and 3.5 (night time) μmol m -2 s -1 in a Combretum micranthum G. Don shrub in Cameroon, whereas maximum values of 9.9 μmol m -2 s -1 are also known for Schima superba Gardner & Champ. trees in the subtropics of southern China (Zhu et al 2011). The maximum sap fl ux density (Js) of 10 g cm² h -1 was relatively low but within the range found for neotropical tree species (Kunert et al 2010).…”
Section: Resultsmentioning
confidence: 79%
“…One study using continuous measurements with open dynamic chambers was conducted in a Schima superba Gardner & Champ. plantation, in the subtropics of southern China (Zhu et al 2011), and another in a subtropical Combretum micranthum G. Don shrub growing in Cameroon (Levy et al 1999). These studies generally found a positive relation between xylem sap fl ux and CO 2 effl ux, but the fi ndings regarding the overall effect of the water transport were quite controversial compared to the results with trees from temperate and boreal forests.…”
Section: Introductionmentioning
confidence: 98%